Be heroic selected minor prophets : Ezra, Haggai, Zechariah - Wiersbe, Warren W. (Colorado Springs, CO Chariot Victor, 1997)
Includes bibliographcal references.
Keywords: Bible. O.T. Ezra -- commentaries; Bible. O.T. Haggai -- commentaries; Bible. O.T. Zechariah -- commentaries